Analysis of Student Responses to Module Development Based on Islamic Integration in Biology Learning in Class XI - Miftahul Khairani; Irda Wahidah Nasution (BEST Journal (Biology Education, Sains and Technology), 2020)
This study aims to determine student responses to the use of Islamic integration-based modules in improving student learning outcomes on the subject of the digestive system in class XI Darul Qur'an Islamic Boarding School. The research method used in this research is descriptive research. The descriptive research used in this research is a survey using a questionnaire. The research instrument used was a student response questionnaire. Analysis of the student response questionnaire showed that 83% of students stated that using the learning module could improve student learning outcomes.